Parámetros básicos de incubación para asegurar la eclosión en los huevos de gallina. - Gualpa García, Angela María (2022)
This bibliographic review document whose subject is basic incubation parameters to ensure hatching in chicken eggs, aims to establish a protocol for the management of incubators for avian production through a correct manipulation of temperature as a basic parameter managing to reduce embryonic death and ensuring the percentage of hatching of eggs, this case study arises from a growing concern about the low percentage of births and early death of the embryo; for this it is necessary to analyze each of the conditions that lead to this problem. The most emerging result of this study is the control of the factors that are affecting embryonic development (temperature, humidity, turning, ventilation), the external conditions that lead to the production area (posture farm) and incubator machines, in other words the success of artificial incubation will depend on the management of the breeders, feeding, disease control, mating activity, body weight and egg quality making them useful for incubation. To have a greater number of chicks born and healthy it is advisable to have an adequate control of all the influential parameters that are affecting embryonic development in addition to applying the golden rules within the hatchery we will thus reduce complications that arise in the future in this process. It is also feasible to carry out a study of the artificial incubation process in different types of birds in order to know which is the most relevant factor in embryonic death.